Insegurança alimentar: uma análise para o nordeste brasileiro - Pinheiro, Laécio de Oliveira (2022)
Thisresearch analyzed the impact of household structure and income, geographic location and social characteristics of household residents on the food security conditions of households in the Northeast region. To this end, the Logit Multinomial model was applied, using microdata from the Household Budget Survey (POF) – 2017/2018, in which the dependent variable consisted of the categories of food security (1 - food security; 2 - mild food insecurity; 3 - moderate food insecurity; 4 -severe food insecurity). The results pointed out that AI is concentrated in specific area such as: rest of the metropolitan region, and to a greater extent in rural areas of the Northeast; that hunger is more present in rented and assigned households; AI is stronger in those households whose walls are made of taipa and wood; when the roof is tile and zinc; AI is more intense when the reference person of the household self-declared black or indigenous and more severe the lower the income for the household; Finally, the results showed that welfare structures impact directly on the living conditions of households. Thus, public policies capable of improving the lives of the population that still resides in houses with mud walls, without piped water, The results pointed out that AI is concentrated in specific area such as: rest of the metropolitan region, and to a greater extent in rural areas of the Northeast; that hunger is more present in rented and assigned households; AI is stronger in those households whose walls are made of taipa and wood; when the roof is tile and zinc; AI is more intense when the reference person of the household self-declared black or indigenous and more severe the lower the income for the household; Finally, the results showed that welfare structures impact directly on the living conditions of households. Thus, public policies capable of improving the lives of the population that still resides in houses with mud walls, without piped water, whose residents have low schooling, whose income is limited and located in remote rural área.